Biochemical correlate of dimorphism in a zygomycete benjaminiella poitrasii: characterization of purified NAD-dependent glutamate dehydrogenase, a target for antifungal agents - Joshi, C. V.; Pathan, E. K.; Punekar, N. S.; Tupe, S. G.; Kapadnis, B. P.; Deshpande, Mukund V. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2013)
The fungal organisms, especially pathogens, change their vegetative (Y, unicellular yeast and H, hypha) morphology reversibly for survival and proliferation in the host environment. NAD-dependent glutamate dehydrogenase (NAD-GDH, EC 1.4.1.2) from a non-pathogenic dimorphic zygomycete Benjaminiella poitrasii was previously reported to be an important biochemical correlate of the transition process. The enzyme was purified to homogeneity and characterized. It is a 371 kDa native molecular weight protein made up of four identical subunits. Kinetic studies showed that unlike other NAD-GDHs, it may act as an anabolic enzyme and has more affinity towards 2-oxoglutarate than l-glutamate. Chemical modifications revealed the involvement of single histidine and lysine residues in the catalytic activity of the enzyme. The phosphorylation and dephosphorylation study showed that the NAD-GDH is present in active phosphorylated form in hyphal cells of B. poitrasii. Two of the 1,2,3 triazole linked beta-lactam-bile acid conjugates synthesized in the laboratory (B18, B20) were found to be potent inhibitors of purified NAD-GDH which also significantly affected Y-H transition in B. poitrasii. Furthermore, the compound B20 inhibited germ tube formation during Y-H transition in Candida albicans strains and Yarrowia lipolytica. The possible use of NAD-GDH as a target for antifungal agents is discussed.
Keywords: Antifungal agent; Benjaminiella poitrasii; Biochemical correlate of dimorphism; Candida albicans; NAD-GDH activity regulation; Yarrowia lipolytica; Yeast-hypha reversible transition

Possible mechanism of antifungal phenazine-1-carboxamide from pseudomonas sp against dimorphic fungi Benjaminiella poitrasii and human pathogen Candida albicans - Tupe, S. G.; Kulkarni, R. R.; Shirazi, F.; Sant, D. G.; Joshi, Swati P.; Deshpande, Mukund V. (Journal of Applied Microbiology, 2015)
AimInvestigation of antifungal mechanism of phenazine 1-carboxamide (PC) produced by a Pseudomonas strain MCC2142. Methods and ResultsAn antifungal metabolite produced by a Pseudomonas was purified and identified as PC. Human pathogenic fungi such as Candida albicans, Candidaglabrata, Cryptococcus neoformans, Fusarium oxysporum, Aspergillus fumigatus and Aspergillus niger were found to be inhibited by PC (MIC90 32-64gml(-1)). Addition of PC (20gml(-1)) during yeast (Y)-hypha (H) transitions inhibited germ tube formation by >90% and >99% in C.albicans National Collection of Industrial Microorganisms (NCIM) 3471 and nonpathogenic model Benjaminiella poitrasii, respectively. After exposure to PC (20gml(-1)), 75-80% yeast cells of B.poitrasii and C.albicans NCIM 3471 showed rhodamine 123 fluorescence indicating high intracellular reactive oxygen species (ROS) production. ROS further led to hyperpolarization of mitochondrial membrane, subsequently induction of apoptosis as evident by externalization of phosphatidylserine, DNA fragmentation, chromatin condensation and finally death in B.poitrasii. In C.albicans NCIM 3471, PC (20gml(-1)) induced apoptosis. ConclusionsThe antifungal effect of PC in B.poitrasii and C.albicans may be due to ROS-mediated apoptotic death. Significance and Impact of the StudyInhibition of Y-H transition of B.poitrasii and C.albicans by PC indicates that it may prove useful in the control of dimorphic human pathogens.
Keywords: Apoptosis; Candida albicans; dimorphism; phenazines; Pseudomonas sp; reactive oxygen species